Selective Antagonism of A1 Adenosinergic Receptors Strengthens the Neuromodulation of the Sensorimotor Network During Epidural Spinal Stimulation - Taccola, Giuliano; Salazar, Betsy Habeth; Apicella, Rosamaria; Hogan, Matthew Kevin; Horner, Philip John; Sayenko, Dimitry (Frontiers in Systems Neuroscience, 2020)
Although epidural spinal stimulation (ESS) results in promising therapeutic effects in individuals with spinal cord injury (SCI), its potential to generate functional motor recovery varies between individuals and remains largely unclear. However, both preclinical and clinical studies indicate the capacity of electrical and pharmacological interventions to synergistically increase engagement of spinal sensorimotor networks and regain motor function after SCI. This study explored whether selective pharmacological antagonism of the adenosine A1 receptor subtype synergizes with ESS, thereby increasing motor response. We hypothesized that selective pharmacological antagonism of A1 receptors during ESS would produce facilitatory effects in spinal sensorimotor networks detected as an increased amplitude of spinally-evoked motor potentials and sustained duration of ESS induced activity. Terminal experiments were performed in adult rats using trains of stereotyped pulses at 40 Hz delivered at L5 with local administration to the cord of 8-cyclopentyl-1,3-dipropylxanthine (DPCPX). We demonstrated that ESS combined with the blockage of A1 receptors increased the magnitude of the endogenous modulation and postponed the decay of responses that occur during ESS alone. Although DPCPX significantly increased the yield of repetitive stimulation in intact spinal cords, effects of A1 antagonism on motor evoked responses after an acute spinal transection were not detected. These studies support future investigation of the optimal dosage, methods of delivery, and systemic effects of the synergistic application of A1 antagonists and spinal stimulation in intact and injured spinal cord.